Home versus away competition: effect on psychophysiological variables in Elite Rugby Union - Cunniffe, B.; Morgan, K. A.; Baker, J. S.; Cardinale, M.; Davies, B. (International Journal of Sports Physiology and Performance, 2015)
This study evaluated the effect of game venue and starting status on precompetitive psychophysiological measures in elite rugby union. Saliva samples were taken from players (starting XV, n = 15, and nonstarters, n = 9) on a control day and 90 min before 4 games played consecutively at home and away venues against local rivals and league leaders. Precompetition psychological states were assessed using the Competitive State Anxiety Inventory-2. The squad recorded 2 wins (home) and 2 losses (away) over the study period. Calculated effect sizes (ESs) showed higher pregame cortisol- (C) and testosterone- (T) difference values before all games than on a baseline control day (ES 0.7-1.5). Similar findings were observed for cognitive and somatic anxiety. Small between-venues C differences were observed in starting XV players (ES 0.2-0.25). Conversely, lower home T- (ES 0.95) and higher away C- (ES 0.6) difference values were observed in nonstarters. Lower T-difference values were apparent in nonstarters (vs starting XV) before home games, providing evidence of a between-groups effect (ES 0.92). Findings show an anticipatory rise in psychophysiological variables before competition. Knowledge of starting status appears a moderating factor in the magnitude of player endocrine response between home and away games.